PENINGKATAN KESEJAHTERAAN KELUARGA INDUSTRI KECIL KUE CUCUR DI DESA GIRICAHYO KECAMATAN PANGGANG KABUPATEN GUNUNGKIDUL YOGYAKARTA - Nurmiasih Nurmiasih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
ass="Apple-interchange-newline"> The objectives of this research are toknow: (1) the information of the income of thesmall industry â€œkue cucurâ€, and (2) the growthof the â€œkue cucurâ€ home industry in GiricahyoVillage. The research used the qualitative approach. The subjects of the research are theresidents of Giricahyo Village who run thesmall industry â€œkue cucurâ€. They are the producers, seller, neighbors of the â€œkue cucurâ€producers and public figure. The research wasconducted in January 2016 to March 2016. Thedata were collected through interviews, observations, and documentations. The data werevalidated using sources triangulation with 3supporting informants. The data analyses usedwere data collecting, data reduction, data display, and conclusion drawing.The results of theresearch are as follows: (1) the effects of theproduction of â€œkue cucurâ€ in Giricahyo Villageis positive to the social and economy sectors. Inthe social sector, the production of â€œkue cucurâ€ creates a new job vacancy and the societycan own new skills in the industrial field andcan socialize with the other societies, prioritizethe cooperation and do not cause the environmental pollution; (2) the growth of â€œkue cucurâ€small industry in Giricahyo village is thechanging of workers, production process, andquality of â€œkue cucurâ€ and until now the industry is still run by almost all heads of the familyin Giricahyo Village.